Determination of organophosphorus pesticides in bovine tissue by an on-line coupled matrix solid-phase dispersion–solid phase extraction–high performance liquid chromatography with diode array detection method - GUTIERREZ VALENCIA, Tania M; GARCIA DE LLASERA, Martha P (Journal of Chromatography A, 2011)
A miniaturized method based on matrix solid-phase dispersion coupled to solid phase extraction and high performance liquid chromatography with diode array detection (MSPD–SPE–HPLC/DAD) was developed for the trace simultaneous determination of the following organophosphorus pesticides (OPPs) in bovine tissue: parathion-methyl, fenitrothion, parathion, chlorfenvinphos, diazinon, ethion, fenchlorphos, chlorpyrifos and carbophenothion. To perform the coupling between MSPD and SPE, 0.05 g of sample was dispersed with 0.2 g of C 18 silica sorbent and packed into a stainless steel cartridge containing 0.05 g of silica gel in the bottom. After a clean-up of high and medium polarity interferences with water and an acetonitrile:water mixture, the OPPs were desorbed from the MSPD cartridge with pure acetonitrile and directly transferred to a dynamic mixing chamber for dilution with water and preconcentration into an SPE 20 mm × 2.0 mm I.D. C 18 silica column. Subsequently, the OPPs were eluted on-line with the chromatographic mobile phase to the analytical column and the diode array detector for their separation and detection, respectively. The method was validated and yielded recovery values between 91% and 101% and precision values, expressed as relative standard deviations (RSD), which were less than or equal to 12%. Linearity was good and ranged from 0.5 to 10 μg g −1 , and the limits of detection of the OPPs were in the range of 0.04–0.25 μg g −1. The method was satisfactorily applied to the analysis of real samples and is recommended for food control, research efforts when sample amounts are limited, and laboratories that have ordinary chromatographic instrumentation.